Pengaruh Struktur Modal dan Profitabilitas Terhadap Return Saham Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) tahun 2018-2021 - Zul Bay, Agus; Kartomo, Kartomo; Kumalasari, Fitri (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
Impact of Capital Structure and Profitability on Stock Return of Manufacturing Companies Listed on the Indonesian Stock Exchange (IDX) in the Period of 2018–2021" is the study's title. This study investigates and summarizes the material influence of capital structure and profitability on stock returns. 65 manufacturing businesses that were listed on the IDX for the years 2018 through 2021 made up the survey sample. Purposive sampling was carried out using a targeted sampling strategy. Using the application program Eviews version 10, analyze the hypothesis using data panel regression analysis. According to the results of the analysis, capital structure (DER) and profitability (ROA) as simulants have no significant effect on stock return, whereas only capital structure as a partial has no significant effect on stock return and profitability as a partial has no significant effect on stock return.